Application of Lattice Boltzmann Method In Predicting Flow Of Shear Driven Cavities - Abdul Munir, Fudhail; Che Sidik, Nor Azwadi; Mohd Azmi, Mohd Irwan; Mohamad Zin, Mohd Rody (Journal of Mechanical Engineering and Technology (JMET), 2015)
In this paper, prediction of fluid flow in shear driven cavities is presented. Lattice Boltzmann Method is used as the alternative to conventional Computational Fluid Dynamics. The geometry of shear driven cavities as well as the Reynolds numbers is varied. The simulation is conducted for three types of shear driven cavities which are square cavity and triangular cavities. The obtained streamline patterns and the centre of vortex for each type is in excellent agreement with benchmark results. It is also found that the streamline patterns is significantly affected by the geometrical shape of cavities.